Analisis Pengaruh Faktor Internal dan Faktor Eksternal terhadap Kinerja Reksa Dana Pendapatan Tetap Syariah - Ikhsan Maulana Rizki; Dimas Sumitra Danisworo; Tjetjep Djuwarsa; Hasbi Assidiki Mauluddi (Journal of Applied Islamic Economics and Finance, 2023)
Sharia fixed income mutual funds are the topic raised by the author because they are mutual funds with the lure of stable returns to investors. Fixed-income mutual funds are one of the biggest contributors to returns to investors,but decreased in 2020. Based on this phenomenon, this final project aims to find out what can affect the performance of Islamic fixed income mutual funds. There are five variables that can be taken based on previous research and classified into internal factors (Mutual fund age, Mutual fund size) and external factors (Inflation, Rupiah exchange rate, and interest rates) to then be tested for their effect on the performance of Islamic fixed income mutual funds as affected variable. The performance of Islamic fixed income mutual funds is measured using the Sharpe method. The sample used in this study were 10 investment manager companies that issued sharia fixed income mutual fund products in the 2016-2020 period and were selected through the Purposive Sampling Technique. The research method used is quantitative-descriptive with a path analysis model. This research is expected to provide information for readers related to sharia fixed income fund